Strategi Pengembangan Obyek Wisata Kahung Desa Belangian Kabupaten Banjar Kalimantan Selatan di Era New Normal - Hendri Aprilliady; Dessy Maulina (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The objectives of this study are: (1) To be able to find out how the condition of the kahung tourism object during the pandemic and new normal era., (2) To be able to formulate the right development strategy to be carried out by the manager of the kahung tourism object in the new normal era.This study uses a descriptive method and also a swot analysis using as many as 6 respondents can be considered to have an influence and play an important role in kahung tourism objects.The results of the study show the condition of the kahung tourism object during the new normal era pandemic, the resulting development strategies are (1) increasing internet network access to make it easier for tourists to use social media directly to introduce interesting kahung tourism objects. (2) Improving the performance of electricity to make it easier for tourists to use electricityand can unite and appeal to tourists directly through digital media.